Identification and characteristics of victims of violence identified by emergency physicians, triage nurses, and the police. Issue 4 (1st December 2002) - Howe, A; Crilly, M
Abstract : Objectives: The objectives of the study were threefold—to evaluate the identification and characteristics of victims of assault who attend an accident and emergency (A&E) department; to compare the total number of assaults recorded in the A&E department with the number recorded by the police; and to assess a system for collecting the location and method of assault. Setting: The A&E department of Chorley and South Ribble Hospital Trust, Lancashire, England. Methods: A three month prospective study was performed. Victims of violence recorded on computer by doctors at discharge were compared with those identified at initial nurse triage. A comparison of police data with the A&E data relating to Chorley residents was performed. Additional information on the method and location of assault was also collected. Results: During the period 305 (2.6%) of the patients attending A&E were identified as having been assaulted. Of the 305 individuals, 236 (77%) were identified by a doctor while 173 (57%) such patients were identified by a triage nurse. A&E identified twice the number of assaults involving Chorley residents as the police. Both men and women were most likely to have been injured on the street (44% and 37% respectively), although a greater proportion of women were injured at home (24%) than men (10%). The majority of injuries were sustained by blows from fists, feet, and heads (73%). Conclusions: A&E doctors identify significantly more patients as the victims of violence than do nurses at triage. Using A&E data identifies assaulted individuals not identified by the police. Computer systems can be used in A&E to provide a more complete picture of the occurrence of violence in the community.